Empirical Investigation of the medium of exchange in Mergers and Acquisitions - REN, JIE (2010)
This paper examines the choice of payment methods in mergers and acquisition (M&A) and the associated post-acquisition performance based on a study of selected 129 transactions during 1990 and 2008.